Traktat Internasional dan Paradoks Globalisasi - Ruru, Emmy Yuhassarie (UI Scholars Hub, 2021)
Since the creation of means of transportation to transfer people from one place to another, there was an indication of the ambiguity of State’s intention in international relation. State’s or Government’s motivation to interact with foreign party has always been triggered by the direct or indirect needs of such State or Government. It can be based on plenty of reasons such as expansion, trade, inexpensive human resources, negotiation, or investment reason and so forth. In many interests, State has acted or functioned as an intermediary. Following the colonization period, each State’s interaction will be based on its free will and sovereignty. Any efforts will be firmed in many international agreements or treaties. This has been emphasized by Adam Smith as ‘the natural tendency of men’, which tends to interact, trade, or exchange.